Influence 5S implementation to higher education institution at Selangor / Nor Azira Ariffin - Ariffin, Nor Azira (2010)
5S program can be defined as Seiri (sort), Seiton (simplify), Seiso (sweep), Seiketsu (standardize) and Shitsuke (sustaining). The purpose of the 5S program is to make the work place clean and reduce of waste. The objective of this study is to study the implementation of 5S in higher education institution in the term of the business performance and to determine critical success factor that influences the success of 5S implementations. The scope of this study is to investigate the influence of 5S in the performance to the higher education institution in Selangor. From the literature reviewed independent variables and dependent variables are verified. These independent and dependent variables were used to develop questionnaire. The questionnaire is use to collect data. The questionnaire is made available in two languages which is Malay and English language. The questionnaire has been sending for experts to validation before the main survey to ensure the validity of the questions. The questionnaire has been distributed in two ways which is sent by email and by self-administered to the respondents. 139 questionnaires has been email but only 10 questionnaires have been replied and 25 questionnaires had been distributed by self-administered but only 22 questionnaire has been returned. The total questionnaires have been replied are 32 questionnaires. After that, data analysis will be analyzed using statistical package for social sciences (SPSS). From the analysis, it shows that government institution are implement 5S program and the private institution not implement 5S program and the most critical success factor that influences the success of 5S implementations is defined